Carbon nanotubes perpendicularly grown on graphene oxide nanosheets derived from metal-organic frameworks: Synergistic reinforcement of poly(l-lactic acid) scaffold - Pei Feng; Feng Yang; Xiaoxin Shi; Shuping Peng; Hao Pan; Cijun Shuai (Journal of Materials Research and Technology)
The construction of the nanohybrid composed of two carbonaceous nanomaterials is a promising strategy to inhibit their aggregation, and effectively exert the advantages of their excellent mechanical properties as reinforcement for polymers. Here, carbon nanotubes (CNTs) were in situ perpendicularly growing on the surface of graphene oxide (GO) through metal-organic frameworks (MOF)-derived strategy by chemical vapor deposition (CVD), aiming to facilitate their dispersion on poly(l-lactic acid) (PLLA) bone scaffold fabricated by selective laser sintering (SLS). Specifically, GO provided nucleation sites for the growth of MOF, and worked as the templates when CNTs grew, in which MOF provided catalysts and carbon sources simultaneously. The precursor was heated to 550 °C and kept for 2 h, then heated to 900 °C and kept for 2 h before cooling. The obtained nanohybrid (GO@CNT) exhibited a superior dispersion state than the pure GO in the scaffold at the same loading, especially when the loading was 0.75 wt%. Adding 0.75 wt% GO@CNT endowed the scaffold with a remarkable increment in tensile strength and compressive strength of 13.36 MPa and 24.72 MPa with enhancement of 55.35% and 18.85%, respectively, compared to the scaffold containing 0.75 wt% GO. A crack extension model combined with experiment results was proposed to better understand reinforcement mechanisms. Additionally, the scaffold containing GO@CNT exhibited benign cytocompatibility with a cell-spreading area of 86.31% and cell density of 564 cells/mm2 after culturing for 5 d according to the results of cell adhesion and immunofluorescence tests, making it a promising candidate for bone defect repair.